Lithology, major, volatile and trace element composition of Hole BT1B samples (Semail ophiolite; ICDP Oman drilling project) - Marguerite Godard; Elliot Carter; Thierry Decrausaz; Romain Lafay; Emma Bennett; Fatma Kourim; Juan Carlos de Obeso; Katsuyoshi Michibayashi; Michelle Harris; Jude Coggon; Damon A H Teagle; Peter B Kelemen; et al. (PANGAEA, 2021)
This database reports the results of bulk rock geochemical measurements realized on 84 rock samples collected from Hole BT1B drilled during ICDP Oman Drilling Project (OmanDP, Kelemen et al. [2020]). 15 samples were collected on-site every 20m during the drilling operations (February-March 2017). 59 samples were selected by the shipboard science party as representative of the different lithologies recovered from Hole BT1B during the description of the cores, on board D/V Chikyu (August 2017). 10 additional listvenites and serpentinites were selected from Sections C5704B-73Z-1 to -75Z-2 (180.01-186.945mbg) for a coordinated on-shore study of the lower serpentinite intervals and neighboring listvenites (thereafter referred to as consortium samples). The purpose of the study was to obtain a high-density and high analytical quality bulk geochemical characterization along the 300.05 meters of continuous cores recovered from OmanDP Hole BT1B, through the transition from the variously carbonated peridotites at the base of the Semail ophiolite mantle section to the underlying metamorphic lithologies. 51 listvenites, 14 serpentinites, and 19 greenshists and greenstones were analyzed. The rock names and grouping by Units were determined on-board D/V Chikyu from macroscopic observations (Visual Core Description; Kelemen et al. [2020]). Major and trace element concentrations were measured by X-ray fluorescence (XRF). XRF analyses of shipboard and on-site samples noted * in the Method columns were realized on-board D/V Chikyu (Note that major oxide concentrations in Kelemen et al. [2020] are recalculated to 100 wt.%) and those noted extdagger in the Method columns were realized at the University of St. Andrews (see Table BT1-T12 in Kelemen et al. [2020]). XRF analyses of consortium samples were realized at Geolabs. FeO concentrations were measured by titration at the University of Lausanne (Switzerland). Total H and C concentrations (noted TH and TC) were determined on-board D/V Chikyu by combustion CHNS elemental analysis (EA) and used to recalculate H2O and CO2 contents. Concentrations of carbon in Ca-carbonates (total inorganic carbon; noted TIC) were determined by coulometry. Trace element compositions were determined using a Quadrupole Inductively-Coupled-Plasma-Mass Spectrometer (Q-ICP-MS) at the University of Montpellier (France). All analyses were performed on samples prepared from non ignited rock-powders, except for XRF major element analyses realized on beads on-board D/V Chikyu. Concentrations are reported in wt.% (10-2g/g) and in ppm (10-6 g/g). Abbreviations: mbg: meters below ground (Chikyu curated depth); Fu-listvenite : fuchsite-bearing listvenite; LOI : Loss on ignition; XRF B : XRF analyses on beads; XRF P : XRF analyses on powder pellets; XRF B/P : XRF major element analyses on beads except for K measured on pellets and recalculated as volatile free; n.a.: not analysed; n.d.: not determined. (Notes, abbreviations & reference at the bottom of the file) extdaggerdbl Sample C5704B-60Z-4-1, 24.0–29.0 cm: Green matrix (Host: Sample C5704B-60Z-4-1, 24.0–29.0 cm - H) crosscut by pink vein (Vein : Sample C5704B-60Z-4-1, 24.0–29.0 cm - V) Reference : Kelemen, P. B., J. M. Matter, D. A. H. Teagle, J. A. Coggon, and the Oman Drilling Project Science Team (2020), Proceedings of the Oman Drilling Project, College Station, TX.